2022
DOI: 10.4103/atm.atm_214_22
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the characteristics of positional and nonpositional sleep apnea patients among the Jordanian population

Abstract: BACKGROUND: Obstructive sleep apnea (OSA) is a common cause of sleep-disordered breathing with a large proportion of the patients exhibiting positional OSA (POSA). In this study, we aimed to evaluate the differences in the demographics, comorbidities, and polysomnographic features between POSA and non-POSA (NPOSA) in a Jordanian sample to further discern the propulsive elements for each group. METHODS: In this study, we evaluated 1037 adult patients with OSA. POSA was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 29 publications
4
6
0
Order By: Relevance
“…Consistent with previous reports, the presence of POSA and e-POSA in our study was associated with milder OSA (lower AHI), lower neck circumference, lower BMI, and lower rate of obesity, as well as with male sex and younger age [ 2 , 7 9 , 12 , 16 , 21 24 ]. Hence, given its association with younger age, lower BMI, and milder OSA severity, POSA is suggested to represent an early stage of the OSA natural history that can develop in non-POSA with increasing age and weight, emphasizing the loss of the positional variability of the obstructive events as disease severity progresses [ 2 , 7 , 9 , 12 , 17 , 25 ]. Supporting the likelihood of POSA patients to become non-POSA with increasing BMI [ 7 ], reduction in weight after bariatric surgery was reported to be associated with an increase in the prevalence of POSA at the expense of non-POSA [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with previous reports, the presence of POSA and e-POSA in our study was associated with milder OSA (lower AHI), lower neck circumference, lower BMI, and lower rate of obesity, as well as with male sex and younger age [ 2 , 7 9 , 12 , 16 , 21 24 ]. Hence, given its association with younger age, lower BMI, and milder OSA severity, POSA is suggested to represent an early stage of the OSA natural history that can develop in non-POSA with increasing age and weight, emphasizing the loss of the positional variability of the obstructive events as disease severity progresses [ 2 , 7 , 9 , 12 , 17 , 25 ]. Supporting the likelihood of POSA patients to become non-POSA with increasing BMI [ 7 ], reduction in weight after bariatric surgery was reported to be associated with an increase in the prevalence of POSA at the expense of non-POSA [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our patients, both POSA and e-POSA were independently associated with lower AHI (total, supine, non-supine, REM, and non-REM). Higher AHI (total, supine, non-supine, REM, non-REM) in non-POSA than in POSA patients has also been reported in other studies, and is suggested to indicate a higher tendency of airway collapse and a more severe disease among non-POSA patients, regardless of the body position during sleep [ 7 , 24 , 26 ]. Moreover, our patients in the e-POSA group had significantly higher TST in the supine position and lower time in the lateral position, while an increase in TST in supine position was also independently associated with e-POSA.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations